A taxonomic revision of the genus Arcynopteryx Klapálek, 1904 (Plecoptera, Perlodidae) - Teslenko, Valentina A. (Zootaxa, 2012)
Four known Arcynopteryx species are redescribed from the types and newly acquired material. Illustrations of the male andfemale genitalia, head and pronotal patterns and eggs are used to support species descriptions. Dictyopteryx compacta(McLachlan, 1872) is transferred to Skwala Ricker, 1943 with the valid name Skwala compacta (McLachlan, 1872) comb.nov., and S. pusilla (Klapálek, 1912) is placed as a junior synonym of that species. For genus Arcynopteryx type species is fixed(under Article 70.3 of the Code) as Arcynopteryx dichroa (McLachlan, 1872), misidentified as Arcynopteryx compacta (McLachlan, 1872) in the original designation by Klapálek (1912).